Development of a Process for Migration of Data from Relational to Non-Relational Database - Noor, Fahad; Padmakumar, Dhason; Vengusamy, Sivakumar (International Journal of Psychosocial Rehabilitation, 2019)
As we know the world is moving towards the cloud computing very fast, it has become the need of every sector. Cloud computing is one of the rapid growing and fast adapting technology so data confidentiality and other issues are also growing and it needs to be resolved and deal on prior basis. The purpose of this paper is to identify reliability issues of cloud based applications in mass media sector of Malaysia and how world have suffered due this problem and as well as how Malaysia can suffer in future if they not constantly work on this domain. This paper consists of various incidents and thorough those we can identify the importance of cloud computing security